Pola Interaksi Guru dan Orang Tua Dalam Mengendalikan Perilaku Belajar Siswa Selama Daring Di SMP 3 Prabumulih - Anggraini, Bella; Darmawani, Evia; Ramadhani, Erfan (Counseling AS SYAMIL: Jurnal Ilmiah Bimbingan Konseling Islam, 2022)
The online learning system certainly makes the condition of student learning behavior unstable, even not a few students experience changes in learning behavior, plus parents who have to replace the role of teachers sometimes experience many difficulties in providing limited time availability. This problem if left unchecked will have a bad impact on students. This is one of the challenges for guidance and counseling teachers, especially at SMP Negeri 3 Prabumulih. The purpose of this study was to obtain an overview of the interaction patterns of teachers and parents in controlling student learning behavior while online at SMP Negeri 3 Prabumulih. This research method is descriptive qualitative. Data collection techniques using observation, interviews and documentation. The main subjects in this study were 1 BK teacher, and 5 students' parents, while the supporting subjects were 5 subject teachers as well as homeroom teachers. Data analysis uses data reduction, data presentation, and drawing conclusions. Source triangulation was carried out as the validity of the data. The results showed that the interaction pattern of teachers and parents in controlling student learning behavior was difficult to establish properly, due to time constraints. This has resulted in the ineffective mentoring of student learning behavior during online learning. To maintain a good cooperative relationship, guidance and counseling teachers, parents, subject teachers as well as homeroom teachers must have time to communicate directly, be open to each other, exchange opinions about the right solution to help the student's problems.